Effect Of Magnetic Nanoparticle Addition On The Superconducting Properties Of Bi-Pb-Sr-Ca-Cu-O - Hussein Baqiah, Hussein Abdullah (2009)

(untitled)
The effect of magnetic nanoparticle additions on the (Bi1.6Pb0.4Sr2Ca2Cu3O10+δ)1-x-(nano M)x with M= Sm2O3, Ho2O3, Nd2O3 and x= 0.0-0.05 systems, sintered at 850°C for 30 hours were investigated by X-ray diffraction techniques, critical temperature measurement, scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX). Magnetic nanoparticles, M= Sm2O3, Ho2O3 and Nd2O3 with 14.8 nm, 18 nm and 49-64 nm particle sizes respectively, were mixed with Bi1.6Pb0.4Sr2Ca2Cu3O10+δ precursor powder prepared by solid state reaction method before the final step heat treatment process. The phase purity, lattice parameters, superconducting properties, surface morphology and grain size were found to be dependent on the magnetic nanopatricles concentration in the sample. The XRD result indicate that the dominant high Tc (Bi2223) phase decrease due to the increase of low Tc phase (Bi2212) with the presence of magnetic nanoparticles with 0<x≤0.02 and the later phase become significant for further addition. The lattice parameters calculated from XRD data show a slight decrease in the c-axis while a-axis increase for initial nanoparticale addition. Lattice parameters decrease monotonically with x≥0.02. The scanning electron microscopy viewing shows platelets like-grain for all samples which is a signature of Bi2223 and Bi2212 phases. The existence of large oriented platelet-like grains that have been observed in pure sample surface, are maintained for sample with 0<x<0.02. Further more the previous samples have small, randomly oriented platelet-like grains that increase with the increase in magnetic nanoparticles content. For x≥0.02 the sample surface becomes more porous with large amount of randomly oriented platelet grains. The elemental analysis by EDX measurement of sample with x=0.05 reveals the existence of nanoparticles that homogeneously distributed in BSCCO matrix. The chemical formula of sample’s elements composition that has been estimated from EDX measurements is in good approximation to that of Bi2223 system with noticeable excess in oxygen ratio which may be due to the existence of magnetic oxide nanoparticles in the sample. All samples exhibit normal metallic behavior above superconducting transition temperature. Zero resistivity temperature Tc (R=0) which is around 102 K for pure sample was found to gradually decrease to lower temperature with magnetic nanoparticle additions and decrease to that of the low-Tc(2212) with x≥0.02. The onset transition temperature Tc is almost the same for sample with 0.005≤x≤0.02 and become lower with higher concentration of addition. The superconducting transition width becomes wider with increase in the magnetic nanoparticles addition. The hole concentration, p, of pure sample under preparation condition is around 0.13. The introduction of magnetic nanoparticles causes a decrease in the hole concentration of Bi2223 system. This decrease characterize by two steps. For initial addition of magnetic nanoparticle, the reduction of hole concentration per change in magnetic nanoparticles addition, Δp/Δx, is more than when x>0.02 for Ho2O3 and Nd2O3 and at x>0.03 for Sm2O3 addition.